Moderating Effects of Exercise Duration and Intensity in Neuromuscular vs. Endurance Exercise Interventions for the Treatment of Depression: A Meta-Analytical Review - Nebiker, Lukas; Lichtenstein, Eric; Minghetti, Alice; Zahner, Lukas; Gerber, Markus; Faude, Oliver; Donath, Lars (Frontiers in Psychiatry, 2018)
Background Exercise training is a beneficial treatment strategy for depression. Previous meta-analytical reviews mainly examined the effect of aerobic exercise on depressive symptoms neglecting com-parisons with neuromuscular training and meta-regression considering relevant exercise training prescriptors such as exercise duration, intensity, number of exercise sessions and fre-quency. Methods A structured literature search was conducted in biomedical and psychological databases and study selection was conducted following the PICOS approach. (Randomized) controlled trials that compared supervised neuromuscular or endurance exercise interventions with an inactive control group (CON) in clinically depressed in- or outpatients over 18 years were included. Eligibility and study quality were evaluated by two independent researchers. Standardized mean differences (SMD) for the reduction of depressive symptoms, measured with different evalua-tion scales (e.g., BDI, HAM-D, PHQ-9, HRSD, MADRS, GDS) were calculated with the ad-justed Hedges’g equation as main outcome for the comparison of endurance and neuromuscular exercise interventions vs. CON. Statistical analyses were conducted using a random effects in-verse-variance model. Multivariate meta-regression analysis was performed in order to examine the modulating effects of exercise training prescriptors. Results 27 trials with 1,452 clinically depressed adults were included. 20 out of 27 included trials reached a PEDro score > 6, representing high-quality. Irrespective of the exercise mode and study quality, large effects in favor of exercise compared to the control condition were found. Compared to CON, sensitivity analyses revealed a moderate to large effect in favor of endur-ance exercise (SMD: -0.79 (90% CI: -1.10, -0.48; p < 0.00001, I2 = 84%) and a large effect size in favor of neuromuscular exercise (SMD: -1.14 (90 CI: -1.50, -0.78); p < 0.00001, I2 = 80%). These effects decreased to moderate for endurance and remained large for neuromuscular trial when considering studies of high quality, indicating a significant difference (p=0.04). Multivariate meta- regression revealed that exercise duration in endurance trials and exercise intensi-ty in neuromuscular trials had a significantly moderating effect. Conclusions Neuromuscular exercise interventions seem to be more effective than endurance exercise inter-ventions. Interestingly, exercise duration and exercise intensity moderated the effect size mean-ingfully. This result might be used on exercise in depression to increase efficacy.